1963
DOI: 10.1126/science.141.3583.810
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Chromosomal Anomalies Induced in Mice by Injection of a Teratogen in Pregnancy

Abstract: The experiments herein reported were undertaken to test whether a selected teratogen that can cause anomalies in 95 percent of fetuses can also cause chromosomal anomalies. 6-Amino nicotinamide was selected as the teratogenic agent, cleft palate as the deformity to be induced, and pregnant outbred females of the 15year-old Phipps mouse colony as the biologic model to be used in the experiments. This agent, this defect, and this animal were chosen because much work had been done on chemical, morphologic, and em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1964
1964
1988
1988

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Ingalls et al (1963) found a high frequency of chromosome fragmentation and polyploidy in cell cultures of tissues adjacent to cleft palate induced in mouse fetuses by 6-aminonicotinamide. Cytogenetic aberrations including mitotic irregularities and karyotype anomalies have been observed in mouse fetuses exposed to trypan blue (Joneja and Ungthavorn, 1968).…”
Section: Discussionmentioning
confidence: 90%
“…Ingalls et al (1963) found a high frequency of chromosome fragmentation and polyploidy in cell cultures of tissues adjacent to cleft palate induced in mouse fetuses by 6-aminonicotinamide. Cytogenetic aberrations including mitotic irregularities and karyotype anomalies have been observed in mouse fetuses exposed to trypan blue (Joneja and Ungthavorn, 1968).…”
Section: Discussionmentioning
confidence: 90%
“…A direct effect on the cell could produce chromosomal anomalies responsible for a deformed structure, as demonstrated with 6-amino nicotinamide in cleft palate [9]. More facts have, however, been assembled concerning interference with the metabolism in the tissue of maldeveloping structures [13,141.…”
Section: Action On Embryonic Endocrine Systemmentioning
confidence: 99%
“…Previous cytogenetic studies have shown that transplacental exposure of rodent embryos to agents that are clastogenic in adult tissues also induces chromosomal aberrations in embryo cells [Ingalls et al, 1963;Tamboise and Tamboise, 1964;Soukup et al, 1965;Roux et al, 1971;Michelmann et al, 1975;Seiber et al, 1978;Basler et al, 19791. Although there is no direct evidence that induction of chromosomal aberrations in individual cells of developing embryos leads to clinical abnormalities, evidence from epidemiological surveys and animal studies indicates that transplacental exposure to known genotoxic agents increases the risk of fetal loss, congenital malformation, malignancy and mutations.…”
Section: Introductionmentioning
confidence: 99%